2017
DOI: 10.3390/molecules22091412
|View full text |Cite
|
Sign up to set email alerts
|

Structure Identification and In Vitro Anticancer Activity of Lathyrol-3-phenylacetate-5,15-diacetate

Abstract: Natural products from the genus Euphorbia show attention-attracting activities, such as anticancer activity. In this article, classical isolation and structure identification were used in a study on Caper Euphorbia Seed. Subsequently, MTT and wound healing assays, flow cytometry, western blotting, Hoechst 33258 staining and fluorescence microscopy examination were applied to investigate the anticancer activity of the obtained compounds. In a result, lathyrol-3-phenyl- acetate-5,15-diacetate (deoxy Euphorbia fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…HuR can bind with DNMT3b and maintain its stability, thus affecting abnormal DNA methylation (Lopez de Silanes et al, 2009). Numerous studies reported that a change of mitochondrial function plays a key role in all kinds of cancers (Tao et al, 2015; Lin et al, 2017b; Zhang J.Y. et al, 2017; Zhang J. et al, 2017), and RBPs involved in the expression and transcription regulation of mitochondrial genes, such as LRPPRC, GRSF1, SLIRP, and other RBPs can interact with mt-RNA to affect the expression and metabolism of mitochondrial transcripts (Dong et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…HuR can bind with DNMT3b and maintain its stability, thus affecting abnormal DNA methylation (Lopez de Silanes et al, 2009). Numerous studies reported that a change of mitochondrial function plays a key role in all kinds of cancers (Tao et al, 2015; Lin et al, 2017b; Zhang J.Y. et al, 2017; Zhang J. et al, 2017), and RBPs involved in the expression and transcription regulation of mitochondrial genes, such as LRPPRC, GRSF1, SLIRP, and other RBPs can interact with mt-RNA to affect the expression and metabolism of mitochondrial transcripts (Dong et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…According to the eligibility criteria, 31 articles were selected for this review, as shown in Figure 1. In the study by Zhang et al, (2017), their aim was to evaluate the antitumor activity of some natural products from the genus Euphorbia. In the study, they used the compound lathyrol-3-phenylacetate-5,15-diacetate (deoxy Euphorbia factor L1, DEFL1).…”
Section: Natural Products and Anticancer Activity Or In Vivo Evaluati...mentioning
confidence: 99%
“…Cancer is one of the leading causes of human diseases and death due to the high rates of morbidity and mortality (14). Currently, chemotherapy, one of the primary therapeutic strategies, exerts its efficacy by multiple mechanisms, such as induction of apoptosis and inhibition of tumor growth (58). Numerous studies have been focused on natural products (912) as they are an important source of novel anti-cancer drugs, targeting various key proteins and the DNA of cancer cells (5,13,14).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, chemotherapy, one of the primary therapeutic strategies, exerts its efficacy by multiple mechanisms, such as induction of apoptosis and inhibition of tumor growth (58). Numerous studies have been focused on natural products (912) as they are an important source of novel anti-cancer drugs, targeting various key proteins and the DNA of cancer cells (5,13,14). Curcumin [(1,7-bis(4-hydroxy-3-methoxyphenyl)-1,6-heptane-3,5-dione] is a yellow pigment present in the rhizome of Curcuma longa Linn (15).…”
Section: Introductionmentioning
confidence: 99%